2009
DOI: 10.1080/03650340902887824
|View full text |Cite
|
Sign up to set email alerts
|

The role of tolerant genotypes and plant nutrients in reducing acid-soil infertility in upland rice ecosystem: an appraisal

Abstract: Acid-soil-related infertility is a major constraint in the humid tropical regions. Soil infertility problems result from low pH, aluminum toxicity, phosphorus deficiency, low silicon and low base saturation, and the interactions between various deficiencies and toxicities. Phosphorus (P) deficiency is identified as a major nutrient deficiency in acid upland soils; and not only are the soils are low in P but also the applied soluble P is rendered unavailable due to reactions with iron and aluminum oxides. Uplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…This could be due to the increased production of organic acids excluded by roots of some crop species that enhance PR dissolution and P availability to the plants (Zapata and Roy 2004). Also, there are varietal differences for tolerance to soil acidity among Oryza sativa rice as reported by Sahrawat et al (2000).…”
Section: Introductionmentioning
confidence: 84%
“…This could be due to the increased production of organic acids excluded by roots of some crop species that enhance PR dissolution and P availability to the plants (Zapata and Roy 2004). Also, there are varietal differences for tolerance to soil acidity among Oryza sativa rice as reported by Sahrawat et al (2000).…”
Section: Introductionmentioning
confidence: 84%
“…The strategy is based on the use of crop cultivars that are adapted to the harsh conditions of the SAT regions especially water stress and nutrient deficiencies. The soil, water and nutrient management practices are developed around the adapted cultivars to realize the potential of the cultivars in diverse production systems (Ae et al 1990;Condon et al 2004;Hiradate et al 2007;Passioura 2006;Bationo et al 2008;Sahrawat 2009;Passioura and Angus 2010). Source: Unpublished results from ICRISAT.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
“…Clearly, the lowland rice ecology provides a better growing soil environment than does the upland ecology for rice growth and yield and Fe or Zn accumulation by the crop. Furthermore, it has been demonstrated that the availability of nutrients especially of Fe and Zn to rice in soils is greatly influenced by water regime (including flooding) and the availability of Fe and Zn is generally favorably affected in the lowland irrigated agroecologies (Ponnamperuma 1972;Gao et al 2006;Sahrawat 2007Sahrawat , 2009). …”
Section: E Nutrient Use Efficiencymentioning
confidence: 99%